Congratulations to team GB, but why should we be so surprised? Olympic medal count can be predicted using logit regression models that include `home advantage` - Nevill, A. M.; Balmer, N. J.; Winter, E. M. (British Journal of Sports Medicine, 2012)
For the vast majority, the London 2012 Olympic Games were a triumph and team Great Britain's (GB) successes in particular were remarkable. The 65 medals won exceeded most people's expectations. The accomplishments were testament to the achievements of athletes and their coaches, a source of delight and pride for spectators and an endorsement for those who provided scientific and medical support.